PD-1/PD-L1 axis induced host immunosuppression via PI3K/Akt/mTOR signalling pathway in piglets infected by Glaesserella Parasuis - Jingyang Li; Siyu Liu; Qiaoli Dong; Yunjian Fu; Yamin Sun; Ronghui Luo; Xinyue Tian; Ling Guo; Wei Liu; Yinsheng Qiu; Qirong Lu; Chun Ye; et al. (BMC Veterinary Research, 2024)
Abstract Glaesserella parasuis, an important respiratory bacterial pathogen, causes Glässer’s disease in piglets, with potential immunosuppression. We established a piglet infection model and explored the immunosuppression mechanism to improve our understanding of the host immune response to G. parasuis. Twenty piglets were randomly divided into two groups (n = 10). The infection group was intraperitoneally challenged with 2 × 108 CFU of G. parasuis in 2 mL TSB. The control group was intraperitoneally injected with equivalent TSB. After 72 h, the piglets were sacrificed, and spleen tissue was collected. PD-1/PD-L1 expression was determined. The splenocytes were isolated to detect CD3+ T, CD3+CD4+ T, CD3+CD8+ T and CD3−CD21+cell differentiation. Via data-independent acquisition (DIA), we compared the proteomics of healthy and infected spleen tissues. Glaesserella parasuis modified CD3+ T, CD3+CD4+ T, CD3+CD8+ T and CD3−CD21+ cell differentiation and PD-1/PD-L1 expression in the spleen. The infection group had 596 proteins with significant differences in expression, of which 301 were significantly upregulated and 295 downregulated. Differentially expressed proteins (DEPs) were mainly related to immune responses. This is the first study on PD-1/PD-L1 expression in the spleen associated with immunosuppression in a piglet model to explore the protein changes related to immune responses via DIA.